A Review of Epidemiological Studies of Asthma in Ghana - Amoah, A.S.; Forson, A.G. (My University, 2013)
Over the past few decades, there has been a dramatic rise in the prevalence of asthma in countries world-wide including Ghana. The purpose of this review article is to explore the available literature on epidemiological studies on asthma conducted in Ghana and what these reveal about the disease in the country. We also examine how these findings fit into the wider context of observations from other African countries and the world. Asthma research in Ghana has focused mainly on children between the ages of 5-19 years with one published study on adult asthmatics. Studies have been conducted in the Greater Accra, Ashanti and Brong-Ahafo regions of the country. From the literature, major factors associated with the observed increase in the prevalence of asthma in Ghana include atopic sensitisation to environmental allergens as well as urbanisation and related lifestyle changes. Other implicated factors were heredity, early life determinants and helminth infections. Future asthma research studies in Ghana should explore the role of environmental air pollutants on the disease’s pathogenesis as well as elucidate the immunological mechanisms by which helminth infections may protect against the disease. In all, additional research is imperative to avert an asthma epidemic in a rapidly urbanizing developing country such as Ghana.